2022
DOI: 10.1111/1365-2745.13901
|View full text |Cite
|
Sign up to set email alerts
|

Consistency of demographic trade‐offs across 13 (sub)tropical forests

Abstract: 1. Organisms of all species must balance their allocation to growth, survival and recruitment. Among tree species, evolution has resulted in different life-history strategies for partitioning resources to these key demographic processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
0
16
3
Order By: Relevance
“…In disagreement with our expectation, our results showed that tree growth rate was neither related to mortality nor recruitment rate (Figure 1a,b). These findings are inconsistent with those of previous studies focusing on undisturbed forests (Gilbert et al, 2006;Kambach et al, 2022;Poorter & Bongers, 2006;Poorter et al, 2008). Our study site is a typical monsoon forest.…”
Section: Demographic Relationships Across Speciescontrasting
confidence: 99%
“…In disagreement with our expectation, our results showed that tree growth rate was neither related to mortality nor recruitment rate (Figure 1a,b). These findings are inconsistent with those of previous studies focusing on undisturbed forests (Gilbert et al, 2006;Kambach et al, 2022;Poorter & Bongers, 2006;Poorter et al, 2008). Our study site is a typical monsoon forest.…”
Section: Demographic Relationships Across Speciescontrasting
confidence: 99%
“…The RF models support wood density and tree species stature as important demographic indicators [43,52,134,136,155], as they are the most important species traits other than species origin. Differing here from past work is that these inventory data span dry to cloud forests, deep alluvial to shallow karst or serpentine soil substrates and a range of land-use histories, regional events and introduced species, all within the same species pool (excepting introduced species).…”
Section: Tree Species Stature Wood Density and Species Originmentioning
confidence: 83%
“…Mortality rates are important to evaluating forest roles in Earth systems, climate change vulnerability, restoration success and sustainable management, and to understanding tree species coexistence [30][31][32][33][34][35][36][37]. A challenge, though, is that tree mortality predictions are highly uncertain, in part because the type, severity and frequency of disturbance, and more stable features like gradients in long-term climate, topography and soils, can all affect mortality [1,8,11,34,[38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to persist in the forest, the pioneers must have a reproductive advantage, ie by producing more seedlings and saplings during their reproductive life than long-lived species do. Rüger et al (2018Rüger et al ( , 2020 and Kambach et al (2022) pursued this possibility by including recruitment rate at the 1 cm size in analyses of demographic axes. This leads to the suggestion that there are species below the growth-mortality axis of Figure 1 that persist in the forest by recruiting well (Rüger et al 2018).…”
Section: Discussionmentioning
confidence: 99%